2018
DOI: 10.18801/jbar.180218.187
|View full text |Cite
|
Sign up to set email alerts
|

Variability, correlation and path analysis in drought tolerant rice (Oryza sativa L.)

Abstract: Yield contributing traits in thirty three rice genotypes were studied for variances, heritability, correlation (genotypic and phenotypic) and path coefficient analysis. The highest phenotypic variation (σ2p), was found for No. of grain per panicle and the lowest was observed in 100 grain wt. High genotypic coefficient of variation (GCV) and phenotypic coefficient of variation (PCV) for No. of unfilled grains per panicle, No. of grains per panicle and grains yield per hill, indicated that selection of these tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 4 publications
11
0
1
Order By: Relevance
“…Plant height registered positive and significant correlation at both levels with panicle length, flag leaf area, secondary branches panicle -1 , number of spikelets and 100-grain weight, while it showed negative and non-significant association with the number of panicles. The results of correlations of plant height are in agreement with the reports of Ria et al (2015) for the number of spikelets; Swapnil et al (2020), Saha et al (2019) and Bhargava et al (2021) for panicle length; Kishore et al, (2018) for 100-grain weight; and Hossain et al (2018) for secondary branches panicle -1 . Plant height showed a negative association with the number of panicles (Ketan and Sarkar, 2014;Kishore et al, 2018).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Plant height registered positive and significant correlation at both levels with panicle length, flag leaf area, secondary branches panicle -1 , number of spikelets and 100-grain weight, while it showed negative and non-significant association with the number of panicles. The results of correlations of plant height are in agreement with the reports of Ria et al (2015) for the number of spikelets; Swapnil et al (2020), Saha et al (2019) and Bhargava et al (2021) for panicle length; Kishore et al, (2018) for 100-grain weight; and Hossain et al (2018) for secondary branches panicle -1 . Plant height showed a negative association with the number of panicles (Ketan and Sarkar, 2014;Kishore et al, 2018).…”
Section: Resultssupporting
confidence: 91%
“…Primary branches panicle -1 showed a positive significant correlation with secondary branches panicle -1 , the number of spikelet, and grain yield panicle -1 and negative non-significant correlation with spikelet fertility. Hossain et al (2018) reported similar results for secondary branches panicle -1 and grain yield panicle -1 . Secondary branches panicle -1 showed a positive significant correlation with number of spikelets and a negative association with spikelet fertility.…”
Section: Resultssupporting
confidence: 68%
“…This shows their true and potent relationship and direct selection in those traits [8] will directly lead to high yield and good Head Rice Recovery. Similar results were reported by Hossain et al, [9]; Parimala et al, [10]; and Samudin et al, [11,12].…”
Section: Path Coefficient Analysis Based On Agro Morphological Traitssupporting
confidence: 91%
“…Very low residual effect (0.0399) indicated that 96 per cent of the variation in grain yield in this population is contributed by the ten characters included in the path analysis. Similar results have been recorded earlier for the number of panicle (Kole et al, 2008;Devi et al, 2017), plant height (Jambhulkar and Bose, 2014;Li et al, 2019), test weight (Kole et al, 2008;Islam et al, 2019), primary branches (Hossain et al, 2018) and secondary branches (Islam et al, 2019).…”
supporting
confidence: 90%
“…This indicated the contributions of these traits towards seed yield. A similar association of grain yield was reported for days to flowering (Adhikari et al, 2018), plant height and test weight (Devi et al, 2017;Tiwari et al, 2019), the number of grains per panicle (Khare et al, 2014;Devi et al, 2017), primary branches (Hossain et al, 2018) and secondary branches . The results of character association implied that plant height, flag leaf area, days to flowering, primary and secondary branches per panicle, spikelet and grain number, spikelet fertility (%) and test weight might be important for determining seed yield in this population of rice.…”
supporting
confidence: 77%